The christian positivism by M.F. Fedorov (Actual Problems of Mind, 2014)
The paper represents «the philosophy of the common task» by M.F. Fedorov as a certain combination of the Christian dogmata with the positivistic philosophy and methodology. The author reinforces of an originality of the Fedorov’s philosophy in considering questions of epistemology, anthropology and social philosophy.
Keywords: "Philosophy of a common cause"; regulation of nature; Christianity; positivism; Christian positivism